Pengeluaran Kesehatan Karena Penyakit TB di Kota Bengkulu - Susilo Wulan (HB PRESS, 2018)
TB creates a substantial and costly economic burden. A consumer perspective, health expenditure include direct costs and indirect costs as well as lost revenues. The burden borne by TB patients will result in the poorest people not being able to afford treatment without reallocation their resources. The aim of study was to calculate the cost of illness by patients and household due to TB in Bengkulu City from pre treatment and treatment period. Study used a cross sectional approach, with smear positive pulmonary TB Patients. Sample of the study was 71 respondents. Cost of TB treatment were measured by direct costs and indirect costs from patient perspective was obtained by conducting interviews and questionnaires. The study found that the direct costs per TB patients in the city of Bengkulu was Rp 2.125.200, -. the causes of high direct costs are hospitalization, treatment and pre-treatment costs, while indirect costs are Rp 5,134,400,-. the higher indirect costs component was patients income loss,followed caregiver income loss. Indirect costs due to premature death was Rp 486,000,000.- and the health expenditure of TB Patients in Bengkulu City was Rp 12.970.900/episode (51%) of the average household income.